1999
DOI: 10.1002/(sici)1097-0010(19990301)79:3<362::aid-jsfa256>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Chlorogenic acids and other cinnamates - nature, occurrence and dietary burden

Abstract: This review defines the range of forms in which cinnamates (p‐coumarates, caffeates, ferulates and sinapates) occur in foods and beverages subdividing them into (i) the classic chlorogenic acids and close allies, (ii) other esters, amides and glycosides, and (iii) transformation products formed during processing. Cinnamate derivatives which would not release cinnamic acid by hydrolysis are excluded. The quantitative data are reviewed concisely and attention is drawn to certain shortcomings, in particular a com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
410
1
23

Year Published

1999
1999
2015
2015

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 1,136 publications
(438 citation statements)
references
References 127 publications
4
410
1
23
Order By: Relevance
“…In fact, only moderate correlation between DPPH and L* values (-0.483, p<0.001) has been found. (Clifford, 1997;Clifford, 1999;Clifford, 2000) up to 95% of the chlorogenic acid content in green coffee with drastic roasting conditions (Trugo & Macrae, 1984) were reported.…”
Section: Influence Of Torrefacto Roasting Process On Phenolic Compounmentioning
confidence: 99%
“…In fact, only moderate correlation between DPPH and L* values (-0.483, p<0.001) has been found. (Clifford, 1997;Clifford, 1999;Clifford, 2000) up to 95% of the chlorogenic acid content in green coffee with drastic roasting conditions (Trugo & Macrae, 1984) were reported.…”
Section: Influence Of Torrefacto Roasting Process On Phenolic Compounmentioning
confidence: 99%
“…coffee, pear, basil, oregano and apple [72]. In 2009 Gugliucci et al demonstrated that caffeic acid in Ilex paraguariensis extracts inhibits the generation of fluorescent AGEs in in vitro experiments [65].…”
Section: Cinnamic Acids and Derivativesmentioning
confidence: 99%
“…They are common plant secondary metabolites found in herbs, fruit, vegetables, grains, tea, coffee beans, propolis, red wine and flavouring agents which form an integral part of the human diet [4][5][6][7]. Bromination of 4,6-dibenzyloxy-3-bromo-2-hydroxyacetophenone with Br 2 in HOAc gave 4,6-dibenzyloxy-3-bromo-2-hydroxyacetophenone and 4,6-dibenzyloxy-3,5-dibromo-2-hydroxyacetophenone in a 90:10 ratio.…”
Section: Discussionmentioning
confidence: 99%